Influence of the addition of antioxidants in vivo on the fatty acid composition of fish fillets - Sant'Ana, L. S.; Mancini, J. (Elsevier B.V., 2000)
In this study, the influence of the addition of antioxidants in vivo on the fatty acid composition of the flesh of a freshwater fish known as pacu (Piaractus mesopotamicus) is verified. Four groups (one being the control group) of juvenile pacu were cultured on isocaloric and isoproteic diets. The lipid source was soybean oil and diets were added with either 100 ppm of alpha-tocopheryl acetate, or 100 ppm of BHT or 1.4 g of rosemary extract (Herbalox(R))/kg diet. The fatty acid composition of the lipids of the different groups was determined before and after irradiation at 2 and 3 kGy, respectively, for the evaluation of the protective effects of the different antioxidants. Similarly, thiobarbituric acid reactive substances (TBARS) were determined from irradiated and nonirradiated samples. The results showed that the use of antioxidants altered the fatty acid composition of the fillets. TEARS and irradiation confirmed their important role in protecting against lipid oxidation. Among all the antioxidants used, tocopherol was the most efficient, as shown by the highest percentage of polyunsaturated fatty acids (PUFA), by the lowest values of TEARS and by the analyses of the individual fatty acid levels at different irradiation doses. Significant statistical differences were observed only in 17% of the fatty acids in the fillets of the groups. (C) 1999 Elsevier B.V. Ltd. All rights reserved.
Keywords: antioxidants; fatty acid; freshwater fish; lipid oxidation